The Influence of the Online Student Facilitator and Explaining (SFAE) Cooperative Learning Model on Learning Outcomes of PAI at SMK Persada, Sukabumi City - Jimatul Arrobi; Endang Supiani; Wida Hartika (research, training and philanthropy institution Natural Aceh, 2023)
The study aims to determine the effect of the Student Facilitator And Explaining (SFAE) type cooperative learning model through the online system on the learning outcomes of class X Pharmacy 1 in PAI subjects at Persada Vocational High School, Sukabumi City. This type of research is based on a quantitative approach with descriptive and inferential/inductive statistical analysis. The research design was quasi-experimental, matching only the pre-test post-test control group design technique. The research process involved an experimental group (Class X Pharmacy 1) with a sample of 28 students who were given treatment and a control group (Class X Pharmacy 2) with a sample of 27 students who were not given treatment. Data collection techniques were library research, documentation, observation, and tests. The test is in the form of multiple choice, and the description refers to the PAI subject matter